A change in composition, a change in colour: The case of limestone sculptures from the Portuguese National Museum of Ancient Art - Dias, L (2020)
To keep the integrity of our common cultural heritage there is a growing need to understand its deterioration mechanisms, so that aesthetical and structural alterations can be predicted and prevented. This work comprises an important contribution to understand the deterioration mechanisms of four limestone sculptures, stored in an indoor museum environment, which is not necessarily an innocuous environment. The limestone sculptures belong to the Portuguese National Museum of Ancient Art and show chromatic alterations and structural damages. The analytical approach allowed the characterisation of several alteration products formed on the sculptures’ surface, which is probably related to the colour alteration of the sculptures. The formation of these alteration products is caused by the stone weathering and biogenic action, resulting from the interaction with the environment. The biogenic agents present and the alteration products formed on the artworks can potentiate the structural damages, resulting in loss of material. Microbiota thriving on the surface of the sculptures was characterised and its cell viability index was determined. The results obtained show that the white hues are related to the efflorescences’ formation, namely calcium sulphates and sodium chlorides, while the red hues are related to the concentration of iron oxides and formation of carotenoids. The characterisation of the microbial population shows that it is mostly prokaryotic and belongs mainly to the class Bacilli.